Application of IoT and Industry 4.0 Components in Textile and Fashion Research - Gurumurthy.B.Ramaiah, Gurumurthy.Kargal.Satyanarayana rao, (International Journal of Advanced Science and Technology, 2020)
IoT and Industry 4.0 components are changing the way the information is communicated with men and machines in textile and fashion activities. The prime objective of this research paper is to identify the recent developments and options available for faculty in universities to develop research projects in textile and fashion technology streams. The Industry 4.0 revolution ideas and concepts and components are discussed in this paper. These include application of new technologies like IoT (Internet of Things) for design and development of devices, artificial intelligence, smart manufacturing, cloud computing, cyber physical system study and implementing these concepts for Textile and Fashion Technology applications. Overall, IoT and Industry 4.0 revolution throws up many challenges for professionals in the way to develop textile and fashion projects.